SOCIAL ENTERPRISES IN ITALY: COPRODUCERS OR STATE AID CLAIMANTS? - Antonucci, Gianluca (European Scientific Journal, ESJ, 2015)
Many countries are developing new strategies for assuring, despite expenses cutting, a good level in public services delivering. In most cases the solution is found through the implementation of policies encompassed in the framework of co-production. The aim of this paper is to show that policies inspired by co-production theories represent a possible solution, but their implementation is not so easy if there is no tradition and no “receptive” environment. Italy represents in this sense an interesting case. The necessity to meet EU standards forced last governments to heavy cutbacks in public spending with many reforms in a country in which there is not such a great tradition in line with co-production theories. In this paper it has been analysed the role of social enterprises as created after the enactment of Decree 155/2006 (fourth and last reform in the Italian social policy system in the last decade). Dimensions, legal forms, number of employees, sectors of activity have been analysed. The analysis of data shows a kind of correlation between regional governments policy decisions and private initiatives regarding social enterprises, with a particular case in Campania Region that influenced the whole system. In conclusion it is affirmed that if there is a lack of tradition in having community services, an ‘imposed’ system inspired to co-production can lead, at least in a first phase, to results that are even worse than the preexisting situation for what regards public spending and lack of high quality services.